HUMANISTIC GEOGRAPHY: PERCEPTION AND SPATIAL REPRESENTATION - Mayer-Malanski, Lawrence (2014)
This article aims to explain the issue of spatial representation in the study of Humanist Geography converging into the process of collective mental mapping. Therefore, we have done a literary search of the authors Maurice Merleau-Ponty, Yi-Fu Tuan and Salete Kozel related to the subject. The research indicates the need for social materialization representation on the part of humanistic geographical studies, which can occur through collective mental maps. Such maps are composed of signs which, after being interpreted, reveal values, identities and aspirations in order to characterize places.